English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

It isn't hard, for you all, apart from me.

Xlog 3=(X+1)log 2

Please help!

Show me the steps...

2007-02-03 15:18:54 · 7 answers · asked by blackmail8549 2 in Science & Mathematics Mathematics

7 answers

xlog3 = (x+1)log2

distribute
xlog3 = xlog2 + log 2
xlog3-xlog2 = log2
x(log3-log2) = log2
xlog(3/2) = log2
x= log2 / log(3/2)
x= 1.7095

2007-02-03 15:26:16 · answer #1 · answered by      7 · 1 0

if you wrote this correctly, this is not a "log" equation, as the log3 and log2 are just constants (numbers). Just imagine how you would solve this if they had written 3 and 2 instead, and do the same thing:

xlog3 = xlog2 +1log2
xlog3 - x log2 = log 2
x(log3 - log2) = log 2
x = log2 / (log3 - log2)

2007-02-03 23:29:32 · answer #2 · answered by grand_nanny 5 · 0 0

Xlog 3=(X+1)log 2
.4771*X=.3010*X+.3010
.1759*X=.3010
X=.3010/.1759=1.7095

2007-02-03 23:28:50 · answer #3 · answered by anonimous 6 · 0 0

Remember that log 3 and log 2 are constants, so first treat them just like any other coefficients:

X*log(3)=(X+1) log(2)
X*log(3)=X*log(2) + log(2)
X*log(3) - X*log(2) = log(2)
X(log(3) - log(2)) = log(2)
x = log(2) / (log(3) - log(2))
x = log(2) / log(3/2)

2007-02-03 23:41:42 · answer #4 · answered by Anonymous · 0 0

xlog(3) = xlog(2) + log(2
x(log(3) - log(2)) = log(2)
x = log(2)/(log(3) - log(2))
x = log(2)/(log(1.5)
x = 1.709511

2007-02-03 23:33:28 · answer #5 · answered by Helmut 7 · 0 0

xlog3 = xlog2 +1log2
xlog3 - x log2 = log 2
x(log3 - log2) = log 2
x = log2 / (log3 - log2)

2007-02-03 23:39:51 · answer #6 · answered by Anne-Ice♥cream 2 · 0 0

first log3 and log2 are just numbers
xlog3=xlog2+log2
xlog3-xlog2=log2
x(log3-log2)=log2
x=log2/(log3-log2)

2007-02-03 23:31:55 · answer #7 · answered by n_ax1000 2 · 0 0

fedest.com, questions and answers